INNOVATIVE PEDAGOGICAL TECHNIQUES FOR TEACHING NEGATIVE EVALUATION VOCABULARY THROUGH THE SEMANTIC FIELD OF ‘UGLINESS’ IN ENGLISH AND UZBEK - QALANDAROVA, Shaxzoda Qurbonboy qizi (The Lingua Spectrum, 2025)
This paper explores the pedagogical potential of the functional–semantic field of “ugliness” in English and Uzbek, proposing an innovative set of techniques for teaching negative evaluation vocabulary. Negative evaluative expressions form an essential component of communicative competence, yet they remain one of the least systematically taught lexical categories. The study argues that combining corpus-based observations, cognitive-semantic principles, and sociolinguistic patterns allows learners to interpret evaluative meanings more accurately, understand their cultural motivations, and apply them appropriately in communication. The paper demonstrates how the semantic field of “ugliness” – with its emotional charge, metaphorical productivity, and cross-cultural variability – can be used to develop stylistic awareness, pragmatic sensitivity, and intercultural literacy.